مشاكل الترجمة السیاسیة الاقتصادیة في مؤتمر "الثروة النفطیة العراقیة": مشاكل الترجمة السیاسیة الاقتصادیة في مؤتمر "الثروة النفطیة العراقیة" (Journal of the College of Education for Women, 2019)
AbstractPolitical economy is one of the important topics in translation. It accompanies twotypes of translation: political and economic translations.The two fields( politics and economics)are inseparable. One completes the other. Onemay read an economic text and find many political terms within it. This proves thefact that the text is not only economic, but also political, i.e. political economy textwhose vocabularies may have no equivalents in the TL (Target Language) and here anumber of strategies are used.This conference had been convened on 29 June/2005 . It is sponsored by The OpenSociety Institute and because of its large information, it is restricted to the two kindsof translation: political and economic translations. Finally , the conclusions have beendrawn.